Clinical Pharmacology Overview of Tislelizumab in Patients With Advanced Tumors With a Focus on Racial Impact - Tian Yu; Chi‐Yuan Wu; Srikumar Sahasranaman; Xianbin Tian; Ying Fei Li; Zhiyu Tang; Yanfei Yang; Ya Wan; Quting Zhang; Patrick Schnell; Ariadna Mendoza‐Naranjo; Ramil Abdrashitov; et al. (Clinical and Translational Science)
ABSTRACT Tislelizumab, an anti‐programmed cell death protein‐1 monoclonal antibody, has demonstrated improved survival over the standard of care for multiple cancers. However, tislelizumab's effectiveness across different racial/ethnicity groups warrants further evaluation. This clinical pharmacology overview includes tislelizumab's pharmacokinetic properties, correlations with efficacy and safety, and immunogenicity, with a focus on racial impact. Non‐compartmental pharmacokinetic analysis was conducted using data from Asian and White patients enrolled in BGB‐A317‐001 and BGB‐A317‐102. Population pharmacokinetic analyses used pooled data from 12 clinical studies to evaluate the impact of intrinsic/extrinsic factors on tislelizumab's pharmacokinetic properties, including race effect. Exposure–efficacy/exposure–safety relationships and immunogenicity assessments were evaluated for the phase III BGB‐A317‐302/‐303 studies. Tislelizumab exhibited dose‐proportional pharmacokinetics, and there were no clinically meaningful differences in tislelizumab's pharmacokinetic parameters at 200 mg once every 3 weeks between BGB‐A317‐001 (n = 12, 83% White patients) and BGB‐A317‐102 (n = 20, 100% Chinese patients); race was not a significant covariate. No clinically relevant exposure–efficacy/−safety relationships were observed in BGB‐A317‐302/‐303. Incidence of anti‐drug antibodies (ADAs) was similar between Asian and White patients. The presence of ADAs was not clinically relevant for tislelizumab's pharmacokinetic properties, efficacy, or safety. There were no differences in tislelizumab's pharmacokinetic or ADA characteristics between Asian and White patients with advanced cancer and no clinically relevant exposure–efficacy/−safety dependency or impact of immunogenicity on efficacy and safety. Data from the extensive clinical program of tislelizumab support the use of tislelizumab across broad patient populations with relevant tumor types.